Fluorescent nanocomposites based on gold nanoclusters for metal ion detection and white light emitting diodes - Zhang, Yongjie; Feng, Ning; Zhou, Shujin; Xin, Xia (Nanoscale, 2021)
Gold nanoclusters (AuNCs) are among the most promising organic-inorganic hybrid luminescent materials for various applications. The current development of AuNCs majorly focuses on controlling their luminescence properties. Herein, we report a new strategy to facilely construct two different nanocomposites featuring enhanced photoluminescence based on mercaptopropionic acid-protected AuNCs (MPA-AuNCs). Through co-assembly with Zn2+ and 2-methylimidazole (2M-IM), the weak luminescence of MPA-AuNCs evolved into either intense blue-green or orange emission at different concentration ratios of additives. HR-TEM and spectroscopic characterization studies revealed that the intense blue-green emission was ascribed to the formation of ZnS quantum dots (QDs) on the outer surface of AuNCs (AuNCs@ZnS), while the strong orange emission originated from the primitive MPA-AuNC core encapsulated by a cubic ZIF-8 shell (AuNCs@ZIF-8). The AuNCs@ZnS nanocomposite was further applied as an exceptional chemical sensor for selective detection of Pb2+ and Fe3+via different quenching mechanisms, and the AuNCs@ZIF-8 composite was applied for fabricating light-converting devices. The co-assembly of AuNCs with Zn2+ and imidazole derivatives provides a facile strategy for acquiring differentiated nanomaterials that have versatile potential applications in chemical detection and light-converting devices.